Development of an Instructional Model Using Design Thinking Approach to Create Thai Identity Products for Undergraduate Students - Rojsangrat , Puchong; Pichayapaiboon, Poonarat; Suwannatthachote, Praweenya (Journal of Education Studies, Chulalongkorn University, 2020)
This research aimed to develop and study the effectiveness of a model with the sample groups of 36 second year students in design education division, King Mongkut’s Institute of Technology Ladkrabang. Research tools included; instructional model, teaching plans, scoring rubrics and questionnaires. Experiment design was one group pretest – posttest design. Design tasks were three Thai identities using different exercises; Hanuman, Ravana, and Garuda VS Naga. Art works of Thai identities on before and after class were assessed by three experts that gave the scores for comparison. The data were analyzed by using means, standard deviation and paired sample t-tests. As a result, the model consisted of 3 principles; (1) creating experience, (2) identity analysis, and (3) synthetic and design. After implementing the model, it was found that the posttest mean scores were higher than the pretest scores at a significant difference of .05 of all exercises.